13‐Hydroxy‐9Z, 11E‐Octadecadienoic Acid Production by Recombinant Cells Expressing Burkholderia thailandensis 13‐Lipoxygenase. (2nd August 2015) - Sim, Dong‐Hyun; Shin, Kyung‐Chul; Oh, Deok‐Kun
Abstract: Linoleate 13‐lipoxygenase from Burkholderia thailandensis was expressed in Escherichia coli for the production of 13‐hydroxyoctadecadienoic acid (13‐HODE), an antiseptic emulsifier. Linoleate 13‐lipoxygenase in cells had higher thermal stability than the purified enzyme. To increase 13‐HODE production, recombinant cells were permeabilized by solvents, detergents, salts, and other chemicals. The enzymatic activity in cells was the highest for permeabilized cells treated with 0.5 M NaCl among the permeabilizers tested. The optimal reaction conditions for the production of 13‐HODE from linoleic acid by permeabilized cells treated with 0.5 M NaCl were at pH 7.5, 25 °C, 20 g/l linoleic acid, 15 g/l cells, 0.15 mM Cu 2+, and 6 % (v/v) methanol in a 100‐ml baffled flask containing a 5‐ml working volume with agitation at 200 rpm. Under these conditions, permeabilized cells produced 15.8 g/l 13‐HODE after 30 min with a conversion yield of 79 % (w/w) and a productivity of 31.6 g/l/h. The conversion yield and productivity of permeabilized cells for 13‐HODE production were higher than those of purified and crude enzymes as well as nonpermeabilized cells. Therefore, permeabilized cells were efficient biocatalysts for 13‐HODE production. To the best of our knowledge, this is the first report of the production of 13‐HODE using cells.